Ethnography of traditional Andean cuisine in the Mantaro Valley, Junin (1928-1990) - Arredondo Baquerizo, Freder Lorgio (2023)
The objective of this review article is to expose essential information about the traditional cuisine of the communities of the Mantaro Valley and place it in the contemporary critical context. For its development, a bibliographic review methodology of local ethnography on food culture was deployed; through bibliographic records of extracted data. Likewise, local disclosure documents were qualified as a primary source, which is the most precise in terms of valuation details of this heritage. From the analysis, we conclude that culinary diversity, explained in techniques and traditional knowledge, are determinants of the identity of its producers.